Manajemen Dan Nilai Ekonomi Pendidikan Dasar Dalam Meningkatkan Mutu Pendidikan - Sri Winarsih (LITERASI (Jurnal Ilmu Pendidikan), 2013)
Management is the all process for carrying out a job through someone else done by two or more people to achieve a state goal which has been determined.  In other word, management is a means of managing the organization. Improving the quality of education need to continuous quality improvement which is a formula or approach should be one of the paradigms of school based management. Improvement of quality approach countinuely is expected to overcome the problem of education quality’s which is not only uses conventional approaches, but in need of an approach in order to optimize resources and fund. It is intended to achieve state objectives effectively, efficiently, creatively and innovatively. The directions approach to improving the quality of the school led to recognize and implement the total quality management. It is an integrated quality management undertaken by all levels of management and the institutional part of the system with the goal of providing outstanding service to customer. Then every school must optimize the management to improve the quality and economic value. Economic value of primary education can provide several benefits including, namely: social and economy benefits.  Keywords: Management, Economic Value of Primary Education Quality.